Diagnosis of soil fertility constraints in bean based cropping systems: review of research results - Mughogho, SK; Wortmann, Charles S. (Southern Africa Development Coordination Conference (SADCC), 1988)
Characteristics of the major soil groups found in bean-growing areas of Africa (Alfisols, Ultisols, Oxisols, Inceptisols) and associated nutritional disorders are discussed. Soil fertility factors affecting bean growth and N fixation, as evidenced in research conducted in Africa, are reviewed as follows: soil type, hydrogen ion concn., excess Mn and Al, and P deficiency. Most of the nutritional disorders of the bean plant found in these regions are linked to low soil pH, Al and Mn toxicities, low available P, P fixation, low CEC, and low availability of basic nutrients. The extent and severity of these problems have not yet been determined; to date, mostly short-term research has been carried out on this topic under controlled environmental conditions. (CIAT)